Co-pyrolysis of eucalyptus and sodium polyacrylate: optimization and synergistic effect - Singh R.K.; Shrivastava D.K.; Sarkar A.; Chakraborty J.P. (My University, 2025)
Co-pyrolysis of eucalyptus and sodium polyacrylate was carried out in a quartz tube reactor and the process was optimized using response surface methodology (RSM). The statistical analysis revealed that both polymer/biomass ratio and temperature had the most significant effect on bio-oil yield (BY) and water content. The optimum condition for co-pyrolysis based on maximum BY and minimum water content was obtained at 550 °C (temperature), 0.54 (polymer/biomass ratio), 60 °C/min (heating rate), and 0.01 min (residence time). Co-pyrolysis at the optimum condition produced 0.36 kg of bio-oil from per kg of the blended feed stock (0.35 kg of sodium polyacrylate and 0.65 kg of eucalyptus). To understand the synergistic effect of co-pyrolysis, experimental values (EXV) were compared with theoretical values (THV). Co-pyrolysis showed negative synergistic effect on BY (EXV = 36.4 wt% and THV = 38.1 wt%) and water content (EXV = 20.8 wt% and THV = 24.7 wt%). However, positive synergistic effect was observed on HHV (EXV = 34.1 and THV = 30.1 MJ/kg) of bio-oil and yield of combustible gases (H2, CO, and CH4). SEM morphology revealed that co-pyrolysis had an appreciable effect on char obtained. FTIR analysis revealed high quality bio-oil from co-pyrolysis containing lesser oxygenated functional groups compared to bio-oil obtained from eucalyptus pyrolysis. GC–MS analysis indicated positive synergistic effect of co-pyrolysis on monoaromatic compounds, acids, and aldehydes while the negative synergistic impact on alcohol, furan, ester, and ketones. © 2020 Elsevier Ltd